Analisis Kelayakan Usaha dan Strategi Pengembangan UMKM Siomay Di Kecamatan Kalianda, Kabupaten Lampung Selatan - Mila Aulia; May Dela Saputri; Nia Endriani; Aryan Ari Sepri YH (Prodi Agribisnis, 2026)
The acceleration of economic growth in Indonesia has been significantly driven by the contribution of the Micro, Small, and Medium Enterprises (MSME) sector, particularly in facilitating job creation and increasing household income. Among the various sectors currently experiencing expansion, the food industry, including the siomay business, has shown positive growth due to its affordability and accessibility to various consumer groups. This study aims to analyze the financial feasibility and formulate development strategies for siomay MSMEs in Kalianda Subdistrict, South Lampung Regency. A quantitative descriptive approach was employed in this research.The results indicate that the business generates daily revenue IDR 505,000, with a selling price of IDR 5,000 per portion and an R/C Ratio of 1.51, indicating that the business is financially feasible. The recommended development strategies include maintaining product quality, improving product and packaging innovation, expanding marketing through digital platforms, enhancing customer service, and managing production costs more efficiently to ensure business sustainability and competitiveness.